Pengaruh CR, ROA dan Ukuran Perusahaan Terhadap Nilai Perusahaan dengan Struktur Modal Sebagai Intervening - Reni Rosita; Khalida Richawati (Universitas PGRI Madiun, 2021)
The purpose of this study is to examine the direct and indirect effects of Current Ratio, Return On Assets and Company Size on Firm Value with the intervening variable Capital Structure. The sample in this study were automotive companies listed on the Indonesia Stock Exchange for the period 2014-2018. The study used purposive sampling technique, in which there were 12 automotive companies that met predetermined criteria. Furthermore, this study applies path analysis using the Eviews program version 8.0 and Microsoft Excel 2016. To determine the direct and indirect effects on linear regression coefficients and to ensure a direct and indirect relationship between the independent variable and the dependent variable through mediation, path analysis is carried out. The results of this study indicate the variable Current Ratio and Company Size have a significant effect on Firm Value, while Return On Assets and Capital Structure Ratio have no effect on Firm Value. Firm size has a significant effect on capital structure, while Current Ratio and Return on Assets have no effect on capital structure. Based on the results of the single test analysis, capital structure cannot mediate between Current Ratio, Return On Assets, and Company Size to Firm Value.